Teaching and learning through drama: exploring the use of process drama to teach history curriculum content - Katz, Lindsey Anne (My University, 2022)
In this research, I investigate the use of enhanced process drama techniques to teach and learn History in South African high schools, particularly the 1976 Soweto Uprising. Rather than using process drama in its conventional form, African indigenous performance modes, such as storytelling, singing, dancing and drumming are integrated into this method in order to enhance process drama and to stimulate relevance in teaching and learning History. The purpose of this study is to address the pedagogical issue relating to the continued reliance on using banking methods to teach History in South African high schools. This has resulted in learner oppression, as learners are positioned as passive consumers of knowledge. Drawing on the theories of critical pedagogy and Africanisation, I argue that actively engaging with History content and learning in a relevant and meaningful manner empowers learners to facilitate their learning as they are positioned as co-producers of knowledge. This study is conducted through a Participatory Action Research approach as this method allows for experimentation using enhanced process drama techniques. The focus of the analysis in this research is to determine whether using enhanced process drama techniques to teach and learn History will transform learning into an empowering experience, stimulate a learner-centred approach to teaching, and improve learners’ understanding. Based on the findings of this research, it is surmised that learning in an experiential manner through enhanced process drama meets the above objectives. This is because process drama enables learners to explore and reflect on historical events from a first-hand perspective.
A Dissertation submitted in fulfilment of the requirements for the degree of Master of Arts by Research to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2022